PENDAPATAN USAHATANI DAN TINGKAT KETAHANAN PANGAN RUMAH TANGGA PETANI LADA HITAM DI DESA SUKADANA BARU, KECAMATAN MARGA TIGA, LAMPUNG TIMUR - Laras Nur Handini; Zainal Abidin; Tubagus Hasanuddin (Lampung University, 2019)
This study aims to analyze black pepper farming income, food security,correlation between income and energy consumption level, and correlation between proportion of food expenditure and food security. This research was held in Sukadana Baru Village, Marga Tiga Subdistrict, East Lampung using a survey method. Fourty three respondents of black pepper farmers were chosen by a simple random sampling. Data of this research were collected in February-March 2018 and analyzed using descriptive qualitative and quantitative analysis, and also Pearson product moment corelation. The study showed that the average income of black pepper farming was Rp23,820,391.86 per year. The total expenditure was Rp1,499,011.00 per month. In addition, there were 70 percent households in food secure category and 30 percent households in food vulnerable category. Proportion of food expenditure has a correlation with food security, and income has a correlation with level of energy consumption. Key words: food expenditure, food security, household income